Analysis of The Implementation of Government Accounting System in The District Office of North Gunungsitoli - Kurniawan Sarototonafo Zai; Dedi Irawan Zebua; Serniati Zebua (CV. Doki Course and Training, 2025)
The purpose of this study is to find out how the government accounting system is implemented at the Gunungsitoli Utara District Office. The population is the financial report at the Gunungsitoli Utara District Office in 2023. The sample taken in this study is the financial report at the Gunungsitoli Utara District Office in 2023. The data analysis technique uses a qualitative descriptive method. Based on the results of the study on the preparation of annual financial reports, the Gunungsitoli Utara District Office has prepared its annual financial report in accordance with Government Regulation Number 71 of 2010 concerning Government Accounting Standards and Regulation of the Minister of Home Affairs Number 13 of 2006 concerning Guidelines for Regional Financial Management, with details 1. The Budget Realization Report presents the realization of income and expenditure compared to its budget for one budget year, 2. The balance sheet presents assets, liabilities and equity funds at the end of the budget year., 3. Notes to the Financial Statements.